The flowering time regulator FLK controls pathogen defense in Arabidopsis thaliana - Fabian, Matthew; Gao, Min; Zhang, Xiao-Ning; Shi, Jiangli; Vrydagh, Leah; Kim, Sung-Ha; Patel, Priyank; Hu, Anna R; Lu, Hua (Plant physiology (Bethesda), 2023)
Abstract Plant disease resistance is a complex process that is maintained in an intricate balance with development. Increasing evidence indicates the importance of posttranscriptional regulation of plant defense by RNA binding proteins. In a genetic screen for suppressors of Arabidopsis (Arabidopsis thaliana) accelerated cell death 6-1 (acd6-1), a small constitutive defense mutant whose defense level is grossly in a reverse proportion to plant size, we identified an allele of the canonical flowering regulatory gene FLOWERING LOCUS K HOMOLOGY DOMAIN (FLK) encoding a putative protein with triple K homology (KH) repeats. The KH repeat is an ancient RNA binding motif found in proteins from diverse organisms. The relevance of KH-domain proteins in pathogen resistance is largely unexplored. In addition to late flowering, the flk mutants exhibited decreased resistance to the bacterial pathogen Pseudomonas syringae and increased resistance to the necrotrophic fungal pathogen Botrytis cinerea. We further found that the flk mutations compromised basal defense and defense signaling mediated by salicylic acid (SA). Mutant analysis revealed complex genetic interactions between FLK and several major SA pathway genes. RNA-seq data showed that FLK regulates expression abundance of some major defense- and development-related genes as well as alternative splicing of a number of genes. Among the genes affected by FLK is ACD6, whose transcripts had increased intron retentions influenced by the flk mutations. Thus, this study provides mechanistic support for flk suppression of acd6-1 and establishes that FLK is a multifunctional gene involved in regulating pathogen defense and development of plants. A canonical flowering regulatory gene, encoding an RNA binding protein, is important for pathogen defense likely through affecting alternative splicing of target genes.